Occurrence of Cu²⁺-resistant microorganisms on Antarctic island Galindez - Tashyreva, G.O.; Matveewa, N.A.; Tashyrev, O.B. (Український антарктичний журнал, 2006)
Copper-resistance of Antarctic microbial communities selected from different samples (sediments, plants etc.) was investigated at Cu²⁺ concentration 5, 25, 100 ppm. It was shown that all samples contain Cu²⁺-resistant microorganisms in large amount about 10⁴–10⁷ CFU/g of sample. There were found 15 morphological types of bacteria, 3 types of actinomycetes, 5 types of fungi. For microorganisms of major part of samples (65%) 100 ppm Cu²⁺ did not show inhibition effect. Було досліджено стійкість антарктичних мікробних угруповань, виділених з різних типів проб (осади, рослинність та ін.) до катіону Cu²⁺ у концентраційному діапазоні 5, 25 та 100 мг/л. Показано, що у вивчених пробах стійкі до міді мікроорганізми мають великий титр, який становить 10⁴–10⁷ колонійутворюючих одиниць/г проби. Розмаїття мідьрезистентних морфотипів для бактерій складає 15, актиноміцетів – 3, грибів – 5. Для мікроорганізмів більшості проб (65%)концентрація 100 мг/л Cu²⁺ не проявляла бактерицидної дії.